School Starting Age and the Crime-Age Profile - Rasmus Landerso; Helena Skyt Nielsen; Marianne Simonsen (Institute for the Study of Labor (IZA), 2015)
This paper uses register-based data to investigate the effects of school starting age on crime. Through this, we provide insights into the determinants of crime-age profiles. We exploit that Danish children typically start first grade in the calendar year they turn seven, which gives rise to a discontinuity in school starting age for children born around New Year. Our analysis speaks against a simple invariant crime-age profile as is popular in criminology: we find that higher school starting age lowers the propensity to commit crime at young ages. We also find effects on the number of crimes committed for boys.
Keywords: I21; K42; 330; criminal charges; school start; old-for-grade; violence; property crime